2021
DOI: 10.1101/2021.03.30.21254339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Food Insecurity in Households of People with Autism Spectrum Disorder during the COVID-19 Pandemic

Abstract: Objectives: To explore differences in food insecurity for individuals and families of people with autism spectrum disorder (ASD) during the COVID-19 pandemic by individual, family, and neighborhood characteristics. Methods: We surveyed a convenience sample of households of people with ASD. We calculated food insecurity using items from the US Census Bureau Household Pulse Survey. Results: Over half of all respondents reported being food insecure (51.8%). Respondents who reported being food insecure were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Food insecurity can also be detrimental to the cognitive development of children, especially those with neurodevelopmental disorders including ASD ( Althoff et al, 2016 ). The percentage of food insecurity status in our study (55–60 %) is comparable to a recent larger study by Autism Speaks that examined food security status among ASD families in November and December, 2020 (52 %) ( Vasudevan et al, 2021 ). Furthermore, while this recent study reported differences in demographic and socioeconomic characteristics by food security status among these families, associations with behavior changes were not examined.…”
Section: Discussionsupporting
confidence: 85%
“…Food insecurity can also be detrimental to the cognitive development of children, especially those with neurodevelopmental disorders including ASD ( Althoff et al, 2016 ). The percentage of food insecurity status in our study (55–60 %) is comparable to a recent larger study by Autism Speaks that examined food security status among ASD families in November and December, 2020 (52 %) ( Vasudevan et al, 2021 ). Furthermore, while this recent study reported differences in demographic and socioeconomic characteristics by food security status among these families, associations with behavior changes were not examined.…”
Section: Discussionsupporting
confidence: 85%
“…A complex array of caregiver demands during COVID-19 (e.g., number of children at home, financial stress, illness) and other unmeasured variables likely contributed to variance in service satisfaction ratings during COVID-19 (e.g. Baweja et al, 2021;Vasudevan et al, 2021). Second, an inherent limitation of an online survey study is that recruitment is limited to individuals who have access to a cell phone or computer and a stable internet connection, which may limit representation of caregivers from lower SES families.…”
Section: Limitationsmentioning
confidence: 99%